The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.3892/or.16.5.1105
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to p16, a cyclin-dependent kinase inhibitor in human malignancies

Abstract: Abstract. The p16 protein is a cyclin-dependent kinase (CDK) inhibitor, which plays an important role in the regulation of the cell cycle by inactivating the cyclin-dependent kinase (CDK) that phosphorylates the retinoblastoma (Rb) protein.Overexpression of p16 protein has been found in many types of human malignancy. Autoantibody response to p16 in cancer has not been reported. This study determined the extent and frequency of autoantibodies to p16 in diverse malignancies. p16 recombinant protein was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 19 publications
1
67
2
Order By: Relevance
“…Overexpression of p16 protein has been reported in several types of cancer, although normal tissues exhibit low or undetectable levels (18,23). This is possibly a feedback reaction to the development of malignancy in the body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of p16 protein has been reported in several types of cancer, although normal tissues exhibit low or undetectable levels (18,23). This is possibly a feedback reaction to the development of malignancy in the body.…”
Section: Discussionmentioning
confidence: 99%
“…As this CDK inhibitor mainly plays a role in suppressing CDK4 and CDK6 activity and arresting cells during the G1 phase of the cell cycle (14,16), it is associated with the unrestrained growth that is the hallmark of cancer (17). A number of studies have suggested that the levels of circulating antibodies to the p16 protein are increased in patients with breast cancer (11,18,19). For example, Looi et al developed an in-house enzyme-linked immunoassay (ELISA) using recombinant p16 protein as antigens to detect anti-p16 IgG levels in the plasma of cancer patients (18) and they observed a significant increase in the prevalence of IgG antibodies to the p16 protein in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase to 44% sensitivity and 97.6% specificity in breast cancer detection was achieved through the successive addition of the three TAAs p53, protein 16 (p16), and avian myelocytomatosis viral oncogene homolog (c-myc; ref. 81). SEREX technology was used by Zhong and colleagues (82) to detect three further breast cancer-associated autoantibodies including serine active site containing 1 (SERAC1), receptor expressed in lymphoid tissues (RELT), and ankyrin repeat and suppressor of cytokine signaling (SOCS) box protein 9 (ASB-9).…”
Section: Breast Cancermentioning
confidence: 99%
“…With the successive addition of TAAs to a final total of seven antigens, there was stepwise increase of positive antibody reactions up to 56.9 percent in HCC. In our recent study, p16, a cyclin-dependent kinase inhibitor, which has been implicated as an important tumor suppressor [33], was evaluated as a TAA and added into our previously constituted mini-array of seven TAAs [24]. As shown in Table 1, the frequency of antibodies to eight TAAs in sera from patients with chronic hepatitis, liver cirrhosis and HCC using Enzyme-linked immunosorbent assay (ELISA).…”
Section: Using a Mini-array Of Multiple Taas To Enhance Antibody Detementioning
confidence: 99%